A norovirus gastroenteritis outbreak in an Australian child-care center: A household-level analysis - Nicolas Roydon Smoll (Public Library of Science (PLoS), 2021)
There is a large burden of norovirus disease in child-care centers in Australia and around the world. Despite the ubiquity of norovirus outbreaks in child-care centers, little is known about the extent of this burden within the child-care center and the surrounding household clusters. Therefore, we performed an in-depth analysis of a gastroenteritis outbreak to examine the patterns of transmissions, household attack rates and the basic reproduction number (R0) for Norovirus in a child-care facility. We used data from parental interviews of suspected cases sent home with gastroenteritis at a child-care center between 24th of August and 18th of September 2020. A total of 52 persons in 19 household clusters were symptomatic in this outbreak investigation. Of all transmissions, 23 (46.9%) occurred in the child-care center, the rest occurring in households. We found a household attack rate of 36.5% (95% CI 27.3, 47.1%). Serial intervals were estimated as mean 2.5 ± SD1.45 days. The R0, using time-dependent methods during the growth phase of the outbreak (days 2 to 8) was 2.4 (95% CI 1.50, 3.50). The count of affected persons of a child-care center norovirus outbreak is approximately double the count of the total symptomatic staff and attending children. In the study setting, each symptomatic child-care attendee likely infected one other child-care attendee or staff and just over one household contact on average.